2012
DOI: 10.1186/1472-6882-12-265
|View full text |Cite
|
Sign up to set email alerts
|

Crude aqueous extracts of Pluchea indica (L.) Less. inhibit proliferation and migration of cancer cells through induction of p53-dependent cell death

Abstract: BackgroundPluchea indica (L.) Less. (Asteraceae) is a perennial shrub plant with anti-inflammatory and antioxidant medicinal properties. However, the anti-cancer properties of its aqueous extracts have not been studied. The aim of this study was to investigate the anti-proliferation, anti-migration, and pro-apoptotic properties of crude aqueous extracts of P. indica leaf and root on human malignant glioma cancer cells and human cervical cancer cells, and the underlying molecular mechanism.MethodsGBM8401 human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 42 publications
1
25
0
2
Order By: Relevance
“…Previous findings have demonstrated the anticancer properties of crude aqueous fraction and ethanol fraction of the P. indica root extract (20). The present study further investigated the suppressive effects of H-PIRE on GBM cells.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Previous findings have demonstrated the anticancer properties of crude aqueous fraction and ethanol fraction of the P. indica root extract (20). The present study further investigated the suppressive effects of H-PIRE on GBM cells.…”
Section: Discussionmentioning
confidence: 77%
“…The P. indica plants used in experiments in this study were collected and verified as described in a previous study (20). The roots of P. indica were prepared as a dried powder and deposited at the National Sun Yat-sen University (Kaohsiung, Taiwan, R.O.C.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated the presence of alkaloids, steroids, terpenoids, flavonoids, phenolic compounds, tannin, lignin in Hemidesmus indicus root extract, flavonoids, phenolic compounds, tannin, saponin, proanthocyanidins in Pluchea indica root extract and essential oil, aristolochic acid, isoaristolochic acid, sesquiterpene, ishwarol, aristololactam, 12-nonacosenoic acid in Aristolochia indica root extract [33][34][35]. These bioactive compounds might be responsible against experimental scorpion envenomation.…”
Section: Discussionmentioning
confidence: 98%